Clinical Profile, Comorbidities, and Outcome of the Unvaccinated and Hospitalized for COVID-19 in Northern Brazil: Retrospective Cohort - , Ana Lúcia Da Silva Ferreira, Daniele Melo Sardinha, Daiane Cristina Viana De Moraes, Maria Raimunda Rodrigues De Oliveira, Mayara Carolina Frazão Viana, Natasha Cristina Oliveira Andrade, Tamires De Nazaré Soares, Ricardo José De Paula Souza E. Guimarães, Luana Nepomuceno Gondim Costa Lima, Karla Valéria Batista Lima (Archives of Current Research International, 2023)
Introduction: Over the course of the pandemic, COVID-19 affected health, the economy and quality of life in Brazil. The worst years for the country were the first and second. There were delays in vaccine purchases for political reasons at the time. The northern region of the country had a higher mortality rate compared to other regions, associated with local vulnerabilities and fragility of surveillance due to geographic and population characteristics. Objective: To investigate the clinical profile, comorbidities, and outcome of unvaccinated people hospitalized for COVID-19 in the state of Pará in 2022. Methods: Retrospective cohort epidemiological study, with data from the national epidemiological surveillance of acute and severe respiratory syndromes. Cases reported in 2022 with vaccinated yes or no field and completed doses were included. Only closed cases cure or death were included. We performed a chi-square test on categorical variables and a Mann-Whitney test on numerical variables. We compared vaccinated VS non-vaccinated; we performed the Odds Ratio in the significant variables. We used the SPSS 20.0 software. Results: The study worked with 2,634 cases of COVID-19 hospitalized in the study period, confirmed by RT-PCR (851/32.30%) and (1,784/67.70%) rapid antigen test. The lethality was (778/29.53%), and those vaccinated with two doses were (1,473/55.90%) and those unvaccinated with no dose (1,162/44.10%). Death represents p- <0.001 (HR 1.306 - CI 1.124/1.517) higher risk of the event occurring in the unvaccinated cases, followed by male sex p-0.004 (HR 1.188 - CI 1.058/1.334). Conclusion: The first cohort in Brazil and in the north of the country to evaluate the clinical profile, comorbidities, and outcome of COVID-19 in hospitalized patients in this Amazon region, which is a region characterized by local vulnerability factors unique to the other regions of Brazil, showed that the unvaccinated were males, younger, with fewer comorbidities, and that they were associated the deaths.